Advances in wound repair and regeneration: Systematic comparison of cell free fat extract and platelet rich plasma - Zhang, Lifang; Hu, Chengjun; Xu, Wenqing; Wu, Dingyu; Lei, Shaorong (Frontiers in Chemistry, 2022)
Background: Previous studies showed Cell free fat extract (CEFFE) and Platelet rich plasma (PRP) could effectively accelerate wound healing. However, the comparative study on curative effect is still lacking. A systematic comparison could provide more theoretical support and laboratory basis for the clinical application of CEFFE and PRP. Objective: To compare the efficacy of CEFFE and PRP in promoting skin wound repair. Methods: CEFFE and PRP were prepared according to the literature. The wound repair related factors were measured and compared. In vitro, the effects of both on cell migration, proliferation and tube formation were compared. In vivo, wound healing rate was measured on the 1st, 3rd, 9th, and 12th days after skin injury and treatment. Then the specimens were cut off for histological analysis. Results: Although the total protein content of PRP was significantly around 19 times higher than that of CEFFE, there was no statistical difference in the content of BDNF, EGF and VEGF between CEFFE and PRP. Even the NT-3 content of CEFFE was just slightly higher than that of PRP. The concentration of b-FGF, HGF and TGF-β and PDGF-BB in PRP is higher than that in CEFFE, but there is only a very small difference between them. In vitro, PRP showed better efficacy than CEFFE in promoting fibroblast proliferation while there was no significant difference in promoting angiogenesis and fibroblast migration. Both PRP and CEFFE could significantly promote wound healing in mice. There was no statistical difference in wound healing between CEFFE and PRP groups in vivo. Immunohistochemical staining of Ki67&CD31 showed that there was no significant difference between PRP and CEFFE groups. Conclusion: The effect of PRP and CEFFE in promoting wound healing was similar. In clinical practice, the acquisition of PRP is relatively more convenient. Containing no cells, CEFFE has the advantage of easier preservation. For patients who have discarded adipose tissue, or contraindications to PRP technology, CEFFE technology may provide a new option for skin wound repair.